Development and Validation of a Cost-Benefit and Satisfaction-Based Instrument for Measuring Higher Education Service Quality - Thu, Huong Tran Thi; Thanh, Tu Nguyen; Lam, Le (International Journal of Learning, Teaching and Educational Research, 2026)
In the context of increasing financial autonomy and growing expectations regarding accountability and return on investment, higher education institutions are increasingly required to demonstrate not only academic quality but also value for money. However, existing higher education service quality models primarily focus on service performance and satisfaction while paying limited attention to students’ cost–benefit evaluations. This study aimed to develop and validate a multidimensional instrument for measuring higher education service quality from a cost–benefit and student satisfaction perspective. A sequential mixed-methods design was employed. The qualitative phase involved literature synthesis, semi-structured interviews, and focus group discussions with 45 students to identify key dimensions of perceived benefits, perceived sacrifices, and satisfaction. The quantitative phase surveyed 703 students from multiple higher education institutions and employed reliability analysis, exploratory factor analysis (EFA), and confirmatory factor analysis (CFA) for psychometric validation. The final instrument consisted of 50 items across six dimensions: Academic Value, Learning Facilities and Resources, Student Support Services, Developmental and Career Benefits, Institutional Responsiveness and Digital Experience, and Perceived Cost and Academic Strain. The model demonstrated strong reliability and acceptable model fit (Cronbach’s alpha = 0.893–0.966; CFI = 0.906; TLI = 0.901; RMSEA = 0.066). The study contributes theoretically by extending higher education service quality measurement through an integrated cost–benefit and satisfaction framework and practically by proposing a standardized Composite Service Quality Score (CSQS) to support benchmarking, quality assurance, and evidence-based institutional governance. https://doi.org/10.26803/ijlter.25.6.4